Novel screening methods — biosensors. (December 2015) - Eggeling, Lothar; Bott, Michael; Marienhagen, Jan
Graphical abstract: Highlights: Transcription factors are approved sensors to monitor intracellular concentrations. Sensors coupled to gfp expression convert concentrations into a graded signal. Combination of FACS and sensors enable selection of target-molecule-producing microorganisms. NAD(P)H-responsive sensors offer generalizable screens for NAD(P)H-dependent enzymes. Recombineering plus sensors unite diversity generation and producer selection. Abstract : Biosensors offer exciting possibilities for improving cells or enzymes as biocatalysts for the synthesis of small molecules. We here review recent progress in the development and the screening applications of transcription-factor-based biosensors. An example is a cofactor-dependent biosensor which provides a generalizable screen for NADPH-dependent enzymes. Another example is the use of a biosensor in combination with recombineering for strain development, thereby expanding the genome engineering techniques to deliver directly bacteria producing small molecules of interest. Biosensor-based techniques in combination with fluorescence-activated cell sorting demonstrate that the gap regarding throughput capabilities of existing methods for the generation of genetic diversity and methods for the subsequent screening can be closed.